Development of a revised taxonomic approach for improving supply chain integration and collaboration - Chen, Ping-Kuo; Lu, Yun Yan (Journal of Business Economics and Management, 2020)
Although integration and collaboration are considered critical factors in supply chain practice, improving integration and collaboration still encounters a dilemma that is ascribable to three problems, i.e., partners’ opportunistic behaviours, the complicated resource distribution and heavy workloads, and large time costs. To solve these problems and effectively improve integration and collaboration, a revised taxonomic approach will be developed in this research. Based on the case of East Asia, the revised taxonomic approach can produce guidelines to help manufacturers well know how to effectively improve integration and collaboration in a sequential manner and avoid encountering the three problems noted above. There are multiple implications of this study; the research results not only develop a new approach by revising theory but also provide convenient tools to help manufacturers effectively improve integration and collaboration when entering different markets. Thus, this study makes great contributions to the field.